Hydrogen adsorption on TaSe2 monolayer doped with light metals: A DFT study. (February 2022) - Yang, Shulin; Zhang, Daiyu; Lei, Gui; Wang, Zhao; Lan, Zhigao; Xu, Huoxi; Gu, Haoshuang
Abstract: The first-principle DFT calculation was applied to study hydrogen adsorption performances of pure TaSe2 and that doped with light metals (Li, Na and K). Li, Na or K could successfully substitute one Se atom to build the stable doped TaSe2 with binding energy of −2.614, −3.303 or −4.172 eV, respectively, higher than their cohesive energy. The H2 interacted weakly with pure TaSe2 but was strongly adsorbed on the doped TaSe2 due to the remarkably improved transferred charges in the doped adsorption systems. The adsorption energy of H2 on Li was calculated to be −0.289 eV, 179.84% and 361.92% higher than that on Na or K, respectively. Then there were four H2 molecules stably adsorbed on the Li-doped TaSe2 monolayer with reasonable average adsorption energy and transferred charges of −0.221 eV and 0.77 e, respectively. Further molecular dynamics simulations showed that four H2 molecules could still be adsorbed on the Li-doped TaSe2 with slightly lower average adsorption energy of −0.189 eV at 300 K. Our study reveals the TaSe2 doped with Li is a promising adsorbent to interact strongly with H2 along with effective modulation of its conductivity and could be used in the area of hydrogen adsorption/sensing. Highlights: Light metals (Li, Na and K) can be successfully doped into TaSe2 monolayer. The adsorption of H2 on TaSe2 is improved via being doped with light metals. H2 interact more strongly with Li-doped TaSe2 compared with Na- or K-doped one. Four H2 can be stably adsorbed on Li-doped TaSe2 with transferred charges of 0.77 e. Li-doped TaSe2 is a potential to effectively adsorb and sense H2 .